2009
DOI: 10.1016/j.jviromet.2009.02.015
|View full text |Cite
|
Sign up to set email alerts
|

Detection of HIV-1 in alternative specimen types using the APTIMA® HIV-1 RNA Qualitative Assay

Abstract: Peripheral blood mononuclear cells (PBMCs), saliva, seminal plasma, and dried blood spots were evaluated as specimen types for the APTIMA HIV-1 RNA Qualitative Assay (APTIMA HIV-1 Assay), which employs a target capture step to recover HIV-1-specific sequences from complex specimen types. Analytical sensitivity studies were carried out using samples that were either diluted or eluted with a buffered detergent and spiked with different concentrations of HIV-1 ranging from 1 to 10,000 copies/mL. PBMC samples spik… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 14 publications
0
15
0
Order By: Relevance
“…usRNA can be easily detected with a seminested or nested quantitative reverse transcription PCR (qRT-PCR) (36-39) or by ddPCR, using a set of primers and probe against Pol or Gag (17, 30, 33, 39). Alternatively, some investigators have adapted commercial quantitative tests for HIV-1 plasma viremia, such as Amplicor (Roche Diagnostics) (40,41) or APTIMA HIV-1 Qualitative assay (Hologic) (42,43) for the quantitation of caRNA. msRNA primers are designed to amplify a region containing the Tat/Rev (or Tat/Nef) exon-exon junction and can be quantified by nested qRT-PCR (36, 38, 39) or ddPCR (17,39,44).…”
Section: Pcr-based Assays To Measure the Latent Reservoirmentioning
confidence: 99%
“…usRNA can be easily detected with a seminested or nested quantitative reverse transcription PCR (qRT-PCR) (36-39) or by ddPCR, using a set of primers and probe against Pol or Gag (17, 30, 33, 39). Alternatively, some investigators have adapted commercial quantitative tests for HIV-1 plasma viremia, such as Amplicor (Roche Diagnostics) (40,41) or APTIMA HIV-1 Qualitative assay (Hologic) (42,43) for the quantitation of caRNA. msRNA primers are designed to amplify a region containing the Tat/Rev (or Tat/Nef) exon-exon junction and can be quantified by nested qRT-PCR (36, 38, 39) or ddPCR (17,39,44).…”
Section: Pcr-based Assays To Measure the Latent Reservoirmentioning
confidence: 99%
“…The pooling of sera or plasma specimens has long been used to improve the accuracy, costeffectiveness, and throughput of screening for many infections (e.g., HIV-1, hepatitis B virus, hepatitis C virus, and West Nile virus) in low-prevalence settings, such as blood banks (4,26). We recently reported methods for pooled analysis of dried blood spots for HIV-1 nucleic acids (1,18).…”
mentioning
confidence: 99%
“…The % clinical sensitivity=number of samples reactive by pooled NAAT/number of samples reactive by IDT-NAAT at the lowest limit of detection × 100. A strong agreement, in analytical sensitivity and specificity was also reported using different pool sizes, specimen types (including DBS) and assays, compared to individual donor testing ruling out the speculated serious negative impact of dilution (optimum at 10 to 45 different donor samples) [4][5][6]8,9,21,26,27,32,34,35]. The sensitivity obviously negatively correlates with the pool size, particularly from 96 to 128.…”
Section: Discussionmentioning
confidence: 63%
“…enrichment by hard spinning) and the incidence of HIV in the targeted population are quite critical to the success and cost effectiveness of MP-NAAT. Low viral load sero-conversion panels are prone to viral RNA dilution of the mini-pools, below the detection threshold of the NAAT, though various studies have confirmed its reliability [4][5][6]8,9,17,21,26,27,32,34,35]. An average clinical sensitivity of 98% was recorded for pooled NAAT using IDT NAAT as v from the studies included in this review.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation